Field effect transistor with thin AlOxNy film as gate dielectric. Issue 2 (5th March 2020) - Firek, Piotr; Szarafiński, Jakub; Głuszko, Grzegorz; Szmidt, Jan
Abstract : Purpose: The purpose of this study is to directly measure and determine the Si/SiO2/AlOxNy interface state density on metal insulator semiconductor field effect transistor (MISFET) structures. The primary advantage of using aluminum oxynitride (AlOxNy) is the perfectly controlled variability of the properties of these layers depending on their stoichiometry, which can be easily controlled by the parameters of the magnetron sputtering process. Therefore, a continuous spectrum of properties can be achieved from the specific values for oxide to the specific ones for nitride, thus opening a wide range of applications in high power, high temperature and high frequency electronics, optics and sensors and even acoustic devices. Design/methodology/approach: The basic subject of this study is n -channel transistors manufactured using silicon with 50-nm-thick AlOxNy films deposited on a silicon dioxide buffer layer via magnetron sputtering in which the gate dielectric was etched with wet solutions and/or dry plasma mixtures. Furthermore, the output, transfer and charge pumping (CP) characteristics were measured and compared for all modifications of the etching process. Findings: An electrical measurement of MISFETs with AlOxNy gate dielectrics was conducted to plot the current-voltage and CP characteristics and examine the influence of the etching method on MISFET parameters. Originality/value: In this report, a flat band and threshold voltage and the density of interface traps were determined to evaluate and improve an AlOxNy-based MISFET performance toward highly sensitive field effect transistors for hydrogen detection by applying a Pd-based nanocrystalline layer. The sensitivity of the detectors was highly correlated with the quality of the etching process of the gate dielectrics.